2018
DOI: 10.2478/fv-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

A Slaughterhouse Survey for Porcine Circovirus Type 2 in Commercial Pigs in Ibadan, Southwest Nigeria

Abstract: Porcine circovirus type 2 (PCV2) is recognized as one of the most important agents of reproductive disorders in gilts and sows worldwide. It is associated with considerable economic losses in the swine industry due to the unthriftiness, and variable morbidity and mortality it causes in pigs. In spite of the devastation caused by this virus to the global pig industry, there is little or no report of its occurrence in Nigeria. Hence, a slaughterhouse based survey was conducted to determine the prevalence of PCV2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…A previous study on the prevalence of PCV2 conducted in Ibadan, Nigeria recorded a prevalence of 1.4 %, based on screening for IgG antibodies against PCV2 [3]. Hence, our study in Abeokuta complements the previous study and provides information on the detection and the prevalence of PCV2 viral DNA, which indicates that both PC- V2a and PCV2b are present in pigs in Nigeria.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A previous study on the prevalence of PCV2 conducted in Ibadan, Nigeria recorded a prevalence of 1.4 %, based on screening for IgG antibodies against PCV2 [3]. Hence, our study in Abeokuta complements the previous study and provides information on the detection and the prevalence of PCV2 viral DNA, which indicates that both PC- V2a and PCV2b are present in pigs in Nigeria.…”
Section: Discussionsupporting
confidence: 77%
“…PCV2 strains have been classified into four main genotypes (PCV2a, PCV2b, PCV2c, and PCV2d) based upon the phylogenetic analyses performed with their full genomes and ORF2 sequences [14,40]. A fifth genotype, PCV2e has also been identified in Mexico and USA [16], all of which have neither been detected nor identified in Nigeria, although anti-PCV2 antibodies have been detected in pig sera at a prevalence of 1.4 % [3].…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, se considera que pese a encontrarse el PCV2 en plasma/suero y a través de las células sanguíneas, su predilección por replicación en macrófagos/ monocitos (Sun et al, 2016) hace más factible utilizar fracciones celulares para la detección de los antígenos virales. En el presente estudio, la presencia de animales positivos a PCV2 sin signos clínicos compatibles con circovirosis porcina sugiere la presencia de infecciones subclínicas o variaciones en la virulencia de las cepas infectantes (Larochelle et al, 2003;Aiki-Raji et al, 2018).…”
Section: Resultados Y Discusiónunclassified
“…In a cross-sectional survey across two southwestern states, 79.2% (89/111) of farmers interviewed were unaware of PCV2 [29]. It is, however, noteworthy that some recent studies have confirmed the presence of PCV2 in the Nigerian pigs [30][31][32], but those studies were limited regarding sample size and area of study coverage. These authors have recommended large-scale epidemiological surveys to understand its national prevalence.…”
Section: Introductionmentioning
confidence: 99%